Field Trial Assessing the Use of Sex-Sorted Semen in Beef Cattle - K. W. Aubuchon; J. A. Odde; C. Bronkhorst; E. M. Bortoluzzi; M. J. Goering; K. E. Fike; K. G. Odde (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:The objective was to evaluate the reproductive performance of sex-sorted semen on beef cows and heifers. Study Description:For this trial, 320 Angus and SimAngus cows and heifers from four groups were used. Group 1 yearling heifers (n = 101) were synchronized using the melengestrol acetate plus prostaglandin F2α(MGA-PGF2α) protocol and Groups 2, 3, and 4 cows (n = 219) were synchronized using the 7-Day CO-Synch + CIDR protocol. Insemination was done with semen from an Angus sire (Group 1 yearling heifers and Group 2 young cows) sorted to contain>90% X-bearing sperm, or a Charolais sire (Groups 3 and 4 mature cows) sorted to contain>90% Y-bearing sperm. Females were bred after visual estrus detection (Group 1 yearling heifers), fixed time artificial insemination (AI; Group 4 mature cows), or split time AI (Group 2 young cows and Group 3 mature cows). The Bottom Line:These results indicate that sex-sorted semen has potential in commercial beef cows and heifers. Increasing carcass weights in the beef industry has caused a greater price spread between steers and heifers. With increasing spread in value between heifer calves and steer calves, opportunity exists for economic gain with “bull” sexed semen, especially in terminal sire programs.
Keywords: beef; sex-sorted semen; reproduction